Kesejahteraan Masyarakat pada Pemerintah Kabupaten/Kota yang Beropini WTP, WDP, Adverse dan Disclaimer di Propinsi Lampung - Khairudin Khairudin; Tia Rizna Pratiwi; Syahril Daud (Politeknik Negeri Lampung, 2019)
The development of audit opinion obtained by the government of regency/city at Lampung Province to date suggests a positive development, with unqualified opinion indicating the highest opinion from the BPK-RI.Â This audit opinion results show significant increase for last few years. Further, there are some local governments that have been for more than three years in a row obtaining the opinion of unqualified opinion. However, the development of a positive audit opinion of the local government is not followed by the development of a positive level of welfare. In fact, the Government of Lampung Province is still ranked the fourth lowest in Sumatra as the poorest province. So the audit opinion which is attached to the local government, in particular the perceived unqualified opinion for this community is not prosperous. This research was conducted on the entire local government in Lampung Province for the period of 2011-2015 with the method of comparative analysis, with the data related to the Human Development Index (HDI) of each District/City Government were obtained from BPS Lampung Province and the data in the form of the audit opinion are sourced from the BPK-RI. The results showed that not all local government obtain unqualified opinion automatically related to the increase of the level of the welfare of the community becomes. For this reason, the local government obtaining the unqualified opinion in the financial management should also improve the welfare of the community through an increase in the budget for education, health and other sectors that directly touch on the improvement of the welfare of the community. It is expected the government succeeded not only in financial management but also in development.Â Keyword: Adverse, Disclaimer, welfare of the community, unqualified opinion, qualified opinion